1983
DOI: 10.1002/maco.19830341002
|View full text |Cite
|
Sign up to set email alerts
|

Radiotracer studies of carbon permeation through oxide scales on commercial high temperature alloys and model alloys

Abstract: Chromia-and alumina-forming commercial high temperature alloys and model alloys were preoxidized at 900 or 1OOO"C in Hz-HzO at a low oxygen potential. The oxide layers were characterized by different methods.The carbon permeation through the oxide layers was studied by exposing the preoxidized specimens to an atmosphere CO-COz-Hz-HzO, tagged with radiocarbon, for long time. The carbon was detected by stepwise polishing and measuring the radioactivity. A slow carbon ingress occurs through chromia layers, differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

1984
1984
2011
2011

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 36 publications
(8 citation statements)
references
References 21 publications
0
7
0
1
Order By: Relevance
“…The maximum carburization depth was observed for alloys containing 11% Cr (McCoy, 1965;Martin and Weir, 1965;Young, 2007). Grabke et al (1983) concluded that carbon containing molecules (CO, CO 2 and CH 4 ) are transport vehicles for carbon. Cracks, voids and defects in the scale are transport routes.…”
Section: Temperature Above 200 • Cmentioning
confidence: 95%
“…The maximum carburization depth was observed for alloys containing 11% Cr (McCoy, 1965;Martin and Weir, 1965;Young, 2007). Grabke et al (1983) concluded that carbon containing molecules (CO, CO 2 and CH 4 ) are transport vehicles for carbon. Cracks, voids and defects in the scale are transport routes.…”
Section: Temperature Above 200 • Cmentioning
confidence: 95%
“…It has been shown [93] that radiotracer carbon in a CO/CO 2 /H 2 /H 2 O gas mixture slowly permeated scales on pre-oxidised Fe-Cr alloys. Even on pure chromium, an apparently dense oxide scale grown in CO/CO 2 gas was found to transmit carbon, forming chromium carbide beneath the oxide [94].…”
Section: The Influence Of Surface Oxides On Metal Dustingmentioning
confidence: 99%
“…Ideally, the scale is impermeable to carbon, and the alloy is protected against carburisation. Although Cr 2 O 3 has negligible solubility for carbon [21], Grabke et al [22] have shown that chromia scales do transmit carbon. Furthermore, it appears from experiments conducted in mixed gases [23] that the carbon permeability of chromia scales depends on gas composition.…”
Section: Carburisationmentioning
confidence: 99%